Black Holes Have More States than Those Defined by the Bekenstein–Hawking Entropy: A Simple Argument - Carlo Rovelli (Universe)
It is often assumed that the maximum number of independent states a black hole may contain is <semantics>NBH=eSBH</semantics>, where <semantics>SBH=A/4</semantics> is the Bekenstein–Hawking entropy and A is the horizon area in Planck units. I present a simple and straightforward argument showing that the number of states that can be distinguished by local observers inside the hole must be greater than this number.